Oleaginous yeast as a component in fish feed - Blomqvist, Johanna; Pickova, Jana; Tilami, Sarvenaz Khalili; Sampels, Sabine; Mikkelsen, Nils; Brandenburg, Jule; Sandgren, Mats; Passoth, Volkmar (Scientific reports, 2018)
This study investigates the replacement of vegetable oil (VO) in aquaculture feed for Arctic char (Salvelinus alpinus) with oil produced by the oleaginous yeast Lipomyces starkeyi grown in lignocellulose (wheat straw) hydrolysate. VO is extensively used to partially replace fish oil in aquaculture feed, which can be seen as non-sustainable. VO itself is becoming a limited resource. Plant oils are used in many different applications, including food, feed and biodiesel. Its replacement in non-food applications is desirable. For this purpose, yeast cells containing 43% lipids per g dry weight were mechanically disrupted and incorporated into the fish feed. There were no significant differences in this pilot study, regarding weight and length gain, feed conversion ratio, specific growth rate, condition factor and hepatosomatic index between the control and the yeast oil fed group. Fatty and amino acid composition of diet from both groups was comparable. Our results in fish demonstrate that it is possible to replace VO by yeast oil produced from lignocellulose, which may broaden the range of raw materials for food production and add value to residual products of agriculture and forestry.
Keywords: Animal Feed; krmivo pro zvířata; Animals; lignin; mastné kyseliny; Triticum; Amino Acids; zvířata; Lipomyces; pšenice; Lignin; pstruh; aminokyseliny; Pilot Projects; Trout; pilotní projekty; Fatty Acids